2000
DOI: 10.1159/000054133
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differences between GPIb Antibody-Induced and Shear Stress-Induced Platelet Aggregates

Abstract: We determined the morphological differences between NNKY5-5-induced and shear stress-induced platelet aggregates using confocal laser scanning microscopy, and investigated the effects of cytokines on these aggregates. As shear stress was increased from low to high, many aggregates were generated. Some platelets and aggregates already exhibited PAC-1 binding at low shear stress. And finally, aggregates were clearly stained by PAC-1 at high shear stress. Low shear stress-induced aggregates included fibrinogen, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies have shown that high sheer stress alone can induce platelet activation and platelet MP formation (32–34), and we have previously shown that the in vitro model used in the current study does cause some activation of monocytes and neutrophils in diluted whole blood but that specific interaction with TNF‐activated EC preconditioned to laminar flow‐induced expression of TF and PAR‐2 on monocytes (11). Here, we have extended these studies and show that interactions with TNF‐activated EC under flow conditions can lead to changes in the proportion of circulating MP defined as <1.0 μm diameter particles within whole blood (25).…”
Section: Discussionmentioning
confidence: 67%
“…Studies have shown that high sheer stress alone can induce platelet activation and platelet MP formation (32–34), and we have previously shown that the in vitro model used in the current study does cause some activation of monocytes and neutrophils in diluted whole blood but that specific interaction with TNF‐activated EC preconditioned to laminar flow‐induced expression of TF and PAR‐2 on monocytes (11). Here, we have extended these studies and show that interactions with TNF‐activated EC under flow conditions can lead to changes in the proportion of circulating MP defined as <1.0 μm diameter particles within whole blood (25).…”
Section: Discussionmentioning
confidence: 67%
“…Recently, a laser light-scattering aggregometer (Kowa PA-100) was developed with the intention of diagnostic uses, , where particular attention was paid to the sensitivity for detecting a very low concentration of AG S at the initial stage of the platelet aggregation process. The number concentration of aggregated particles was given solely as counts of scattering signals/time, while an attempt was made to estimate the particle size from scattering intensity on the basis of Mie's theory .…”
Section: Introductionmentioning
confidence: 99%
“…The number concentration of aggregated particles was given solely as counts of scattering signals/time, while an attempt was made to estimate the particle size from scattering intensity on the basis of Mie's theory . In these studies, thus, a quantitative description for time-dependent platelet aggregation with respect to the size and the number concentration of aggregates had not yet been successful. As a result, the previous laser light-scattering aggregometer is excellent in diagnostic and biomedical uses, but for use in a quantitative study of the platelet aggregation there is still great room for improvement in the way of analyzing scattering data.…”
Section: Introductionmentioning
confidence: 99%